2000
DOI: 10.1159/000053280
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Ursolic Acid (Merotaine) Increases Ceramides and Collagen in Human Skin

Abstract: Skin wrinkling and xerosis associated with aging result from decreases of dermal collagen and stratum corneum ceramide content. This study demonstrates that ursolic acid incorporated into liposomes (MerotaineTM) increases both the ceramide content of cultured normal human epidermal keratinocytes and the collagen content of cultured normal human dermal fibroblasts. In clinical tests, Merotaine increased the ceramide content in human skin over an 11-day period. Merotaine has effects on keratinocyte di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 10 publications
(15 reference statements)
3
10
0
Order By: Relevance
“…MMPs are proteolytic enzymes that degrade native collagens and other extracellular matrix components. Previous studies are in agreement with tests done by the cosmetic industry, which indicated that ursolic acid stimulated collagen production in cultured fibroblasts (4) and increased the production of ceramides in human epidermal keratinocytes and human skin (5) . Also, ursolic acid triggered the apoptotic intrinsic pathway characterized by Bax overexpression, concomitant Bcl-2 underexpression, and subsequent collapse of mitochondrial membrane potential (6,7) .…”
supporting
confidence: 88%
“…MMPs are proteolytic enzymes that degrade native collagens and other extracellular matrix components. Previous studies are in agreement with tests done by the cosmetic industry, which indicated that ursolic acid stimulated collagen production in cultured fibroblasts (4) and increased the production of ceramides in human epidermal keratinocytes and human skin (5) . Also, ursolic acid triggered the apoptotic intrinsic pathway characterized by Bax overexpression, concomitant Bcl-2 underexpression, and subsequent collapse of mitochondrial membrane potential (6,7) .…”
supporting
confidence: 88%
“…Both ursolic acid liposomes and retinoic acid decreased markers of keratinocyte differentiation (keratin 1, keratin 10, and involucrin) in cultured normal human epidermal keratinocytes. 144 Skin wrinkling and xerosis associated with aging result from decreases of dermal collagen and stratum corneum ceramide content. Ursolic acid incorporated into liposomes increases both the ceramide content of cultured normal human epidermal keratinocytes and the collagen content of cultured normal human dermal fibroblasts.…”
Section: 3the Treatment Of Wrinkles With Ursolic Acid In Clinical mentioning
confidence: 99%
“…Recently vitamin C has been shown to activate PKC, increase ceramide synthesis and improve the ceramide subspecies profile in epidermal skin equivalents [133]. Yarosh and Brown [134] also demonstrated that ursolic acid increased ceramides in human skin. For a complete analysis of agents that stimulate lipid biosynthesis see Table II.…”
Section: Epidermotherapy: Lipid Synthesis Enhancersmentioning
confidence: 99%